The Influence of Word Search Puzzles Media in the English Vocabulary Mastery of Grade Ten Students - Akkas, Nahdia; Wahyudin, Wahyudin; Patmasari, Andi; Darmawan, Darmawan (Journal of English Language and Education, 2025)
This study aims to prove whether the influence of Word Search Puzzles media can prove the mastery of English vocabulary of tenth grade students at MAN 1 Kota Palu. This study is a quantitative study, and researcher used a quasi-experimental design with pre-test and post-test to measure students' mastery of English vocabulary. The results of the study showed a significant influence in students' mastery of English vocabulary after the application of Word Search Puzzles media. The collected data were analyzed statistically to determine significant differences between the experimental group and the control group. The data showed that the average post-test score of the experimental group (77.05) was higher than the control group (44.50). In addition, based on the hypothesis analysis, it showed that T-test T-table (2.48 2.027). This means that the research hypothesis is accepted Thus, it can be concluded that Word Search Puzzle media significantly improves students’ vocabulary mastery.